The Representation of the Southern Italian Mother in Popular Italian Cultural Productions - Brunetti, Francesca (Journal of Gender and Power, 2023)
In this article I discuss how the southern Italian woman’s motherhood has been represented in popular Italian cultural productions. By analyzing movies, novels and television shows I select six typologies of southern Italian mothers, and I address how these typologies, with the exception of the last one, present the southern Italian woman, the terrona, in a negative way. The most common typology is the one of being loving and affectionate while also being underprivileged and uncapable of providing sustenance to their children. The second typology is the one of being oppressive and controlling. The third one is about being powerful and strong and to have her authority rejected by her children. The forth one is about being selfish and uncaring, and the fifth is about being dangerous and violent. In the last typology, I discuss two rare positive representations of southern Italian motherhood where she is loving and caring while also strong, capable to take care of herself and to transmit to her children a positive approach to life. These positive representations of southern Italian mothers, however, address these women as lacking social power because they belong to the working class. The positive traits of being caring, optimistic, financially established and socially influential never emerge all together in popular representations of the southern Italian motherhood. Rather, caring southern Italian mothers are usually represented as poor and marginalized while wealthy and powerful southern Italian mothers are portrayed as selfish and uncaring. This data denounces the necessity of creating alternative representation of southern Italian mothers where they are addressed as positive and caring while also satisfied, well-off and powerful.